PENGARUH DISIPLIN KERJA, KECERDASAN EMOSIONAL DAN IKLIM ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT SUMBER CIPTA MULTINIAGA DENPASAR - Putu Devi Wilia Dewantari; I Gede Gama; Gde Bayu Surya Parwita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Employee performance is very important in the organization's efforts to achieve its goals. Good and professional performance by all employees (the company) is one of the goals of HR management. This study aims to determine the effect of work discipline, emotional intelligence and organizational climate on employee performance at PT. Sumber Cipta Multiniaga Denpasar. This research was conducted at PT. Sumber Cipta Multiniaga Denpasar using a sample of 80 employees. The sampling technique used was the census method. Data collection was carried out through interviews and questionnaires. The data analysis technique used is multiple linear regression analysis processed using SPSS version 23 software. Based on the results of the analysis, this study shows that work discipline, emotional intelligence and organizational climate have a positive and significant effect on employee performance at PT Sumber Cipta Multiniaga.